Power Construction in the Practice of Buying and Selling Land - Nurnaningsih Nurnaningsih; I Made Pria Dharsana (International Journal of Law, Crime and Justice, 2025)
Delegating power in land transactions plays a crucial role in ensuring legal certainty and protection in Indonesia. This study examines the legal implications of granting power of attorney in land sales, focusing on the prohibition of absolute power as regulated under the Instruction of the Minister of Home Affairs No. 14 of 1982 and Government Regulation No. 24 of 1997. The research identifies issues arising from the misuse of power of attorney, which is often used to disguise unlawful land ownership transfers. Using a normative legal research method, this study analyzes legislative provisions, judicial interpretations, and case law to evaluate the legality of power of attorney in land transactions. The findings reveal that despite legal prohibitions, loopholes allow misuse, creating risks of legal uncertainty. The study concludes that stricter enforcement and regulatory refinements are needed to prevent such misuse and enhance legal protection for all parties involved.